2016
DOI: 10.1111/vsu.12437
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interlocking a Universal Hip Cementless Stem on Implant Subsidence and Mechanical Properties of Cadaveric Canine Femora

Abstract: ObjectiveTo determine if an interlocking bolt would limit subsidence of the biological fixation universal hip (BFX®) femoral stem under cyclic loading and enhance construct stiffness, yield, and failure properties.Study DesignEx vivo biomechanical study.AnimalsCadaveric canine femora (10 pairs).MethodsPaired femora implanted with a traditional stem or an interlocking stem (constructs) were cyclically loaded at walk, trot, and gallop loads while implant and bone motions were captured using kinematic markers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…In this study, subsidence was lower after implantation of BFX Lateral Bolt than after implantation of BFX Collared and traditional BFX in dogs treated with THR. The reduced subsidence was likely due to immediately increased construct stability provided by the bolt early in the postoperative period, prior to bone ingrowth . The authors expected that the BFX Collared would also be more resistant to subsidence compared with the traditional BFX, but this supposition was not supported by the results of this study because similar subsidence was identified between BFX Collared and traditional BFX.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In this study, subsidence was lower after implantation of BFX Lateral Bolt than after implantation of BFX Collared and traditional BFX in dogs treated with THR. The reduced subsidence was likely due to immediately increased construct stability provided by the bolt early in the postoperative period, prior to bone ingrowth . The authors expected that the BFX Collared would also be more resistant to subsidence compared with the traditional BFX, but this supposition was not supported by the results of this study because similar subsidence was identified between BFX Collared and traditional BFX.…”
Section: Discussionmentioning
confidence: 63%
“…The BFX EBM lateral bolt stem (BFX Lateral Bolt) is a recently developed femoral stem modification that incorporates a lateral bolt into the traditional BFX cementless stem. This lateral bolt stem accepts a stabilizing bolt that is threaded into the femoral stem from the lateral side and achieves angular stability via a conical coupling design . The lateral bolt stem was designed to make the stem more resistant to subsidence and rotation after THR .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the retrospective nature of the study, there was variability in the implants used. All dogs were implanted with BioMedtrix BFX implants; however, newer modified versions of the BFX stems were used in some dogs, including the use of a BFX stem with lateral locking bolt in two dogs and a collared stem in another two dogs, both designed to help prevent stem subsidence (Table ) . The only stem complication (subsidence) noted was in a dog with a stem not specifically modified to help prevent subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…All dogs were implanted with BioMedtrix BFX implants; however, newer modified versions of the BFX stems were used in some dogs, including the use of a BFX stem with lateral locking bolt in two dogs and a collared stem in another two dogs, both designed to help prevent stem subsidence (Table 1). 30,31 The only stem complication (subsidence) noted was in a dog with a stem not specifically modified to help prevent subsidence. Assessment of dogs with pseudoacetabulum treated by THA with no variability in implants used may give a truer reflection of the complication rate associated with these cases.…”
Section: Discussionmentioning
confidence: 99%